2016
DOI: 10.1080/07421656.2016.1166832
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cortisol Levels and Participants' Responses Following Art Making

Abstract: This quasi-experimental study investigated the impact of visual art making on the cortisol levels of 39 healthy adults. Participants provided saliva samples to assess cortisol levels before and after 45 minutes of art making. Participants also provided written responses about the experience at the end of the session. Results indicate that art making resulted in statistically significant lowering of cortisol levels. Participants' written responses indicated that they found the art-making session to be relaxing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(101 citation statements)
references
References 26 publications
4
63
2
4
Order By: Relevance
“…Lastly, unlike in previous studies where we found no impact of prior experience (Kaimal et al, 2016), here we found that a few outcomes (negative affect, creative agency and self-efficacy) tended to be slightly better for participants with some experience with artmaking. Note that we were not referring to perceived skills, only whether they had any prior experience.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Lastly, unlike in previous studies where we found no impact of prior experience (Kaimal et al, 2016), here we found that a few outcomes (negative affect, creative agency and self-efficacy) tended to be slightly better for participants with some experience with artmaking. Note that we were not referring to perceived skills, only whether they had any prior experience.…”
Section: Discussioncontrasting
confidence: 99%
“…The salivary biomarker data suffered from an even smaller sample size due to problems with the data collection for several of the participants who did not generate enough saliva to enable analysis; thus, little could be determined from these results. Further studies with a larger sample are necessary to determine if change might occur in caregiver's biomarkers after art therapy as we had observed in a general adult population (Kaimal et al, 2016). Some participants had particular difficulty producing sufficient saliva prior to the session, potentially related to high initial levels of stress as stress can decrease saliva production (Slavish et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite these challenges, some recent work has shown promise-although sample sizes remain small. In a 2014 study, Girija Kaimal of Drexel University, an art therapist who also holds a doctorate in human development and psychology, investigated the effect of a single 45-minute art therapy session on stress in 39 healthy adults (3). She and her team sampled the saliva of participants before and after the session to test levels of cortisol, a stress-related hormone.…”
Section: Bridging Fieldsmentioning
confidence: 99%
“…The study was conducted with participants between the ages of 18-59 years old and results showed that among 75% of the participants Cortisol levels were lowered after one 45 minute session. Originally Drexel University thought that the materials and age could affect the outcome of the study; Clay and marker projects vs. a collage project, however, in the end the results did not support this initial idea (Kaimal, Ray, & Muniz, 2016).…”
Section: Gross Motor Activitiesmentioning
confidence: 94%